Rancang Bangun Dan Analisa Bisnis Minimum Viable Product Distro Management System (Dimans.co.id) - I Putu Agus Priska Suryana; I Putu Satwika; I Gusti Bagus Made wiradharma; Wisnu Adhi Saputra (Primakara University, 2019)
Football is one sport that really enjoy doing around the world, football is played by millions of people, whether male or female, young or old, tall or short people person so football became the most popular sport in the world. Almost everyone can play football, because football is a sport that is simple and fun to play. PSSI is currently being frozen variety of ways to treat a football longing to do and can be a land for business. Not deny various types of businesses associated with this sport can achieve success quickly. Some types of businesses regarding football that can be considered success is like selling merchandise, clothes, shoes, games, watch together as well as in the field of information such as website. Of the few that came the idea to create a website that will accommodate football news, statistics, schedules and watch the game together along with point quiz challenge which is provided on the website.